Modern tendencies in developing net of settlements of Nova Varoš district - Vujadinović Snežana M.; Gajić Mirjana R. (Glasnik Srpskog Geografskog Društva, 2004)
Analysis of demographic and functional characteristics of the settlements in Nova Varoš district points to polarization development and the character of the Net of settlements. Nova Varoš plays dominant role in spatially functional settlement organization. With development of certain rural settlements - subcenters, favorable conditions for optimal exploitation of resources oh Nova Varoš district would be made as well as for its more even socio-economical development.